Biomass derived porous carbon (BPC) and their composites as lightweight and efficient microwave absorption materials. (15th February 2021) - Guan, Hongtao; Wang, Qiuyue; Wu, Xiaofen; Pang, Jie; Jiang, Zhiyang; Chen, Gang; Dong, Chengjun; Wang, Lihong; Gong, Chunhong
Abstract: With the pursuit of high-efficiency microwave absorbing materials (MAMs), biomass derived porous carbon (BPC)-based materials have attracted a great deal of attentions due to their plentiful resources, low density and highly environment-friendly. The microwave absorption of BPC composites is closely correlated to their composition, surface chemical activity, microstructures, and pore size, which are in turn decisively determined by the biomass precursors and subsequent carbonization or activation. In this article, we provide a timely and comprehensive review on recent achievements for the microwave absorption properties of various BPC-based MAMs. Firstly, the general synthesizing approaches for carbon materials from various biomass sources, especially in relation to the carbonization and activation are summarized. Then, based on the basic microwave absorption theory, the performances of pure BPC served as microwave absorber are presented. After that, the strategies to improve the microwave absorption properties of BPC including heteroatom doping and the formation of composites with magnetic metals, metal oxides, polymers, and so on, are discussed as well. Finally, we provide discussions and prospects for the development of BPC as lightweight and efficient MAMs in the further. It is believed that the current progress in experimental investigations combined with theoretical predictions will greatly promote the design and development of lightweight and efficient MAMs. Moreover, as an important type of MAMs, views on the challenges and prospects of BPC-based MAMs are proposed as well. Graphical abstract: Image 1 Highlights: We provide a timely and comprehensive review on recent achievements of various BPC-based MAMs. The performances of both pure BPC and various BPC composites served as microwave absorber are presented. The current progress in experimental investigations combined with theoretical predictions are proposed. Views on the BPC-based MAMs will greatly promote the design and development of lightweight and efficient MAMs.